Executive compensation, firm performance, and chaebols in Korea: evidence from new panel data - Takao Kato; Woochan Kim; Ju Ho Lee (Institute for the Study of Labor (IZA), 2005)
This paper provides the first rigorous econometric estimates on the pay-performance relations for executives of Korean firms with and without Chaebol affiliation. To do so, we have assembled for the first time panel data (that provide information not only on executive compensation and firm performance but also on Chaebol affiliation) for 246 firms that were included in KOSPI200 for at least two consecutive years from 1998 to 2001. Contrary to a popular belief that Korean corporate governance and the structure of Korean executive compensation is considerably different from elsewhere in the West, we find that cash compensation of Korean executives is statistically significantly related to stock market performance and that the magnitude of the sensitivity of pay to stock market performance is comparable to the U.S. and Japan. Perhaps even more importantly, further analysis reveals for the first time that such overall significant executive pay-performance link is driven by non-Chaebol firms and that no such link exists for Chaebol firms. The evidence is consistent with the recent literature on the nature of Chaebols in Korea and the current corporate governance reform efforts in Korea that are aimed mostly at Chaebol firms.
Keywords: M52; M12; G30; G15; J33; O53; 330; executive compensation; firm performance; corporate governance; Korea; Chaebols; Führungskräfte; Gehalt; Unternehmensentwicklung; Corporate Governance; Konglomerat; Südkorea